Reuse Strategies of Urban Areas and Built Heritage: Case Study of Karbala Old City - Zainab Al Ameen; Maria Glòria Font Basté; Núria Martí Audí (Environmental Science and Sustainable Development, 2025)
Preserving urban heritage and identity is a pressing issue in cities undergoing rapid development. The city center of Karbala, home to one of the holiest shrines for Shia Muslims, faces significant pressure from its annual influx of over 20 million pilgrims. This necessitates development initiatives focused on creating vast open areas around the shrines, which involve demolishing approximately half of the old city. This research critically assesses potential problems stemming from this approach and explores alternative solutions. Through analyzing the traditional urban fabric, including its distinctive characteristics, existing open spaces, land use, and pilgrimage movement patterns, and drawing insights from similar practices, it uncovers possibilities within the current city center and strategies to address the demands of increasing visitor numbers without compromising the invaluable historic urban fabric. The research advocates for the pivotal role of "Reuse" in preserving the historic urban fabric, complemented by its rehabilitation and restoration. By utilizing the existing urban fabric, the city can reduce the necessity for extensive demolition and redevelopment, thus safeguarding its distinctive urban character and identity. Additionally, it underscores the essentiality of prioritizing adaptability and flexibility, particularly in light of the significant transformations experienced during the annual event.